Charaterization of Leishmania major Friedlin Telomeric Terminus - Miguel Angel Chiurillo; José Luis Ramírez (Memorias do Instituto Oswaldo Cruz, 2002)
Here we have characterized Leishmania major (Friedlin) telomeric terminus (the very end) using recombinants obtained by a vector-adaptor cloning protocol. As in L. donovani, the last nine nucleotides of L. major terminus are 5'-GGTTAGGGT-OH 3', differing from Trypanosoma cruzi and T. brucei terminus 5'GGGTTAGGG-OH 3', thus indicating that these sequences are genus specific. We have also made a comparative analysis between L. major and L. donovani telomere-associated sequences, and described a novel non-repeated telomeric associated sequence common to L. major low molecular weight chromosomal bands.